Preclinical efficacy and safety of adeno-associated virus 5 alpha-galactosidase: A gene therapy for Fabry disease - Jolanda M.P. Liefhebber; Giso Brasser; Elisabeth A. Spronck; Roelof Ottenhoff; Lieke Paerels; Maria J. Ferraz; Lukas K. Schwarz; Nikoleta Efthymiopoulou; Chi-Lin Kuo; Paula S. Montenegro-Miranda; Melvin M. Evers; Johannes M.F.G. Aerts; et al. (Molecular Therapy: Methods & Clinical Development)
We developed a novel adeno-associated virus 5 gene therapy (AAV5-GLA) expressing human alpha-galactosidase A (GLA) under the control of a novel, small and strong, liver-restricted promoter. We assessed the preclinical potential of AAV5-GLA for treating Fabry disease, an X-linked hereditary metabolic disorder resulting from mutations in the gene encoding GLA that lead to accumulation of the substrates globotriaosylceramide and globotriaosylsphingosine, causing heart, kidney, and central nervous system dysfunction. Effects of intravenously administered AAV5-GLA were evaluated in (1) GLA-knockout mice aged 7–8 weeks (early in disease) and 20 weeks (nociception phenotype manifestation) and (2) cynomolgus macaques during an 8-week period. In both species, AAV5-GLA was observed as safe, generated detectable vector DNA and mRNA levels in liver, and produced stable enzyme activity in liver and plasma. In mice, dose-dependent transgene enzyme activity, cross-correction (substrate reduction) in kidney and heart, and improved nociception lasted over 6 months. Moreover, after delayed administration when animals displayed the nociception phenotype, target organ enzyme activity was present, and accumulated substrates were reduced. Given the strong, durable expression of active GLA with this promoter and favorable profile of adeno-associated virus 5-based gene therapy in humans, AAV5-GLA warrants further investigation in clinical trials for Fabry disease.